Is the PPnBM Incentive Useful? A Perspective from Business Actors - Nugraheni, Agustina Prativi; Cahyonowati, Nur (Jati: Jurnal Akuntansi Terapan Indonesia, 2023)
This study aims to explore how employers view the provision of PPnBM incentives by the government. This research contributes to the entrepreneur's perception of PPnBM incentives. This research uses an interpretive case study method using data in the form of reports on targets and sales in 2021 and 2022, as well as interviews related to the perceptions of business actors. The results show that, according to entrepreneurs, this PPnBM incentive does not provide enough stimulus for product sales. Therefore, there is a need for efforts from within the company itself in addition to the PPnBM incentive stimulus.